Detection of Stem Cell Transplant Rejection with Ferumoxytol MR Imaging: Correlation of MR Imaging Findings with Those at Intravital Microscopy - Daldrup-Link, Heike E. (Radiology, 2017)
PURPOSE: To determine whether endogenous labeling of macrophages with clinically applicable nanoparticles enables noninvasive detection of innate immune responses to stem cell transplants with magnetic resonance (MR) imaging. MATERIALS AND METHODS: Work with human stem cells was approved by the institutional review board and the stem cell research oversight committee, and animal experiments were approved by the administrative panel on laboratory animal care. Nine immunocompetent Sprague-Dawley rats received intravenous injection of ferumoxytol, and 18 Jax C57BL/6-Tg (Csf1r-EGFP-NGFR/FKBP1A/TNFRSF6) 2Bck/J mice received rhodamine-conjugated ferumoxytol. Then, 48 hours later, immune-matched or mismatched stem cells were implanted into osteochondral defects of the knee joints of experimental rats and calvarial defects of Jax mice. All animals underwent serial MR imaging and intravital microscopy (IVM) up to 4 weeks after surgery. Macrophages of Jax C57BL/6-Tg (Csf1r-EGFP-NGFR/FKBP1A/TNFRSF6) 2Bck/J mice express enhanced green fluorescent protein (GFP), which enables in vivo correlation of ferumoxytol enhancement at MR imaging with macrophage quantities at IVM. All quantitative data were compared between experimental groups by using a mixed linear model and t tests. RESULTS: Immune-mismatched stem cell implants demonstrated stronger ferumoxytol enhancement than did matched stem cell implants. At 4 weeks, T2 values of mismatched implants were significantly lower than those of matched implants in osteochondral defects of female rats (mean, 10.72 msec for human stem cells and 11.55 msec for male rat stem cells vs 15.45 msec for sex-matched rat stem cells; P = .02 and P = .04, respectively) and calvarial defects of recipient mice (mean, 21.7 msec vs 27.1 msec, respectively; P = .0444). This corresponded to increased recruitment of enhanced GFP– and rhodamine-ferumoxytol–positive macrophages into stem cell transplants, as visualized with IVM and histopathologic examination. CONCLUSION: Endogenous labeling of macrophages with ferumoxytol enables noninvasive detection of innate immune responses to stem cell transplants with MR imaging. (©) RSNA, 2017 Online supplemental material is available for this article.